2009
DOI: 10.1038/aps.2009.176
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin improves insulin sensitivity in mice with obesity induced by monosodium glutamate

Abstract: Aim: To examine the mechanisms underlying the effects of atorvastatin on glucose and lipid metabolism. Methods: Mice with insulin resistance and obesity induced by monosodium glutamate (MSG) were used. Atorvastatin (80 mg·kg -1 ·d -1 ) or vehicle control treatment was given orally once a day for 30 days. Plasma levels of total cholesterol, triglycerides, low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and free fatty acids were monitored. Serum insulin and glucose conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 31 publications
3
20
0
1
Order By: Relevance
“…57 In spite of that, our MSG mice did not display altered serum cytokine levels as compared with lean controls, corroborating a previous study which showed that 6-month-old MSG mice had higher hepatic but unaltered serum levels of TNFα and IL-6. 58 Indeed, MSG rodents have hypercorticosteronemia, 59 which suppresses systemic pro-inflammatory cytokines production. 60 However, MSG rodents also have resistance to corticosterone in adipose tissue, 61 and corticosterone excess can induce oxidative stress 62 and lipid accumulation 63 in hepatocytes, which might explain the paradoxical inflammation upon these tissues.…”
Section: Discussionmentioning
confidence: 99%
“…57 In spite of that, our MSG mice did not display altered serum cytokine levels as compared with lean controls, corroborating a previous study which showed that 6-month-old MSG mice had higher hepatic but unaltered serum levels of TNFα and IL-6. 58 Indeed, MSG rodents have hypercorticosteronemia, 59 which suppresses systemic pro-inflammatory cytokines production. 60 However, MSG rodents also have resistance to corticosterone in adipose tissue, 61 and corticosterone excess can induce oxidative stress 62 and lipid accumulation 63 in hepatocytes, which might explain the paradoxical inflammation upon these tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the beneficial effects of pioglitazone have been primarily observed on triglycerides in both animal [ 19 ] and humans [ 20 , 21 ] with minimal effects on other lipid components [ 20 , 21 ]. Similarly, the lipid lowering effects of atorvastatin in rats and mice have consistently been documented only on triglycerides [ 10 , 22 , 23 ]. Also, in most studies statins do not decrease LDL levels in these animals.…”
Section: Discussionmentioning
confidence: 99%
“…MSG increases insulin resistance and thereby increases blood insulin level, blood glucose plasma levels and also an increase in the plasma total cholesterol, triglycerides, low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C) and free fatty acid levels. It also reduces the cortisol induced lipolysis (Zhang et al, 2010).…”
Section: Bioscience Biotechnology Research Communicationsmentioning
confidence: 99%